UPAYA MENINGKATKAN KEMAMPUAN MEMBACA PERMULAAN SISWA KELAS 1B MENGGUNAKAN MEDIA HUPARO - Afifah, Hanum; Rasidi, Rasidi; Wijayanto, Sukma; Supriyati, Lilis (Universitas Muria Kudus, 2023)
The purpose of this study is to find out how to use the learning media Huparo (Huruf On Rotating Wheel) can improve the reading ability of the beginning class 1B SDN Percobaan 2 Depok on Indonesian language subjects. The research method used is Class Action Research. (PTK). This class action research model uses the Kemmis Mc Taggart model that consists of four steps, namely: planning, action and observation, and reflection. The study was conducted in August-December 2023 at SDN Percobaan 2 Depok with a total of 28 students in the strange semester of the academic year 2023/2024. Data collection techniques are carried out using tests, observations of students and teachers, interviews, and documentation. Data analysis techniques use pre-cycle scores and post test results of cycle 1 and cycle 2 students of class 1B SDN Percobaan 2 Depok. The result showed students' ability to read early in Indonesian language learning using Huparo (Huruf On Rotating Wheel) teaching media in Class 1B SDN Percobaan 2 Depok in the strange semester of the 2023/2024 academic year experienced an improvement in students' learning outcomes from pre-cycle by 57.14%, cycle 1 by 71.31% and cycle 2 by 91.61%. So, the learning media is very accurately used in a classroom learning that is passive and the student's starting reading ability is low.